Prediksi Paket Return Menggunakan Metode Decision Tree Menerapkan Algoritma C4.5 Berbasis Website - Oskar Maha Kasi; Agus Muliantara (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
The development of e-commerce technology has provided significant benefits in facilitating online transactions. However, one of the problems that is often faced by e-commerce companies is the management of return packages, where customers return goods that have been purchased. In order to optimize the package return management process, an effective prediction method is needed to estimate the possibility of returning packages by customers. With a website-based package return prediction system, e-commerce companies can take appropriate actions to manage return packages more efficiently. For example, they can adjust their inventory strategy, improve product quality, or provide special promotional offers to customers who have a high probability of returning packages. This can help increase customer satisfaction, reduce the cost of managing return packages, and increase the overall operational efficiency of the company.